Little Freddie two pants : (the dog with too many pants) [book with audioplayer] - Daywalt, Drew ([Library Ideas, LLC], 2025)
"A laugh-out-loud funny picture book about a dog who doesn't know how many pairs of pants to wear (or where to wear them!) by the #1 New York Times bestselling author of The Day the Crayons Quit. One pair of pants? Two pairs? Three? How many pants should Little Freddie wear? And where should he put them? What about underpants? Where do they go? In a book with text and art that are sure to induce giggles, Drew Daywalt and Lucy Ruth Cummins settle the age-old question: Do a dog's front legs deserve pants, too?"--